The English language teacher's handbook : how to teach large classes with few resources - Baker, Joanna. (Continuum, 2000)
Introduction. Introducing change. Background to teaching English. Organising lessons to teach new language. Organising lessons to improve language skills. Ideas for reaching vocabulary. Ideas for teaching grammar...